Study on the Safety Thickness of Three Zones against Fault Water Inrush: Case Study and Model Development - Yongqian Wang; Benshui Yang; Jun Zhang (Journal of Engineering, 2024)
The raising and flowing of groundwater caused by coal mining threaten the stability of mining faces, which cause casualties and machine damage accidents. Among the above accidents, the water inrush disaster caused by the water-rich water-conducting fault zone is the largest. Considering the complexity of geological structure and the suddenness of water inrush, reserving a reasonable thickness of waterproof coal pillars in front of the fault tectonic belt can effectively predict and control the occurrence of water inrush. The excellent adaptability of the numerical model to the geological conditions makes it an effective research method for simulating waterproof coal pillars. Based on the analysis of the background of on-site mining, this paper proposes a three-zone waterproof coal pillar calculation theory and establishes a numerical model for comparative analysis. The comparison results show that (1) the elastic-plastic theory and fracture theory can be used to calculate the thickness of the disturbed zone and the water-resisting zone, and the thickness of the fractured zone is positively correlated with the accuracy of the existing detection technology and equipment. (2) For the numerical model results, the increase of tangential stress is positively correlated with the distance of coal seam mining and the thickness of fault; the large plastic zone of the fault causes a higher increase in pore pressure, which ultimately increases the risk of water inrush. (3) The two results are in good agreement. The theoretical results have a safety margin, indicating that the three-zone theory is reasonable, which are used to guide the actual mining of the project to ensure the smooth passage of the project through the fault area.